2011
DOI: 10.1074/jbc.m110.192930
|View full text |Cite
|
Sign up to set email alerts
|

Loop L5 Acts as a Conformational Latch in the Mitotic Kinesin Eg5

Abstract: All members of the kinesin superfamily of molecular motors contain an unusual structural motif consisting of an ␣-helix that is interrupted by a flexible loop, referred to as L5. We have examined the function of L5 in the mitotic kinesin Eg5 by combining site-directed mutagenesis of L5 with transient state kinetics, molecular dynamics simulations, and docking using cryo electron microscopy density. We find that mutation of a proline residue located at a turn within this loop profoundly slows nucleotideinduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 29 publications
2
42
0
Order By: Relevance
“…Multiple attempts at deforming the ΔL5-domain into a configuration that would stably interact with the nucleotide failed. Interaction of L5 with the nucleotide site is further supported by studies suggesting that mutations of L5 perturb the Eg5 kinetic cycle [1, 12, 1518, 22]. …”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Multiple attempts at deforming the ΔL5-domain into a configuration that would stably interact with the nucleotide failed. Interaction of L5 with the nucleotide site is further supported by studies suggesting that mutations of L5 perturb the Eg5 kinetic cycle [1, 12, 1518, 22]. …”
Section: Discussionmentioning
confidence: 85%
“…EM reconstructions of microtubule-bound Drosophila kinesin-5 motor KLP61F likewise indicated that L5 undergoes a microtubule-binding dependent interaction with the α3-helix that was postulated to be involved in the transition between force-generating and diffusional modes of MT binding [45]. Spectroscopic and biochemical data have additionally linked L5 to the force-generating cycle through changes in the conformation of the neck-linker [1, 15, 46] that have been proposed to be modulated via interaction with the α3-helix and concomitant perturbations of Switch 1 by the α3-helix [15]. We observed only minimal interaction of L5 with the α3-helix in our simulations (a single interaction with Arg221 in two of the six simulations).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16, 23, 30 Loop 5 undergoes dynamic conformational shifts during the ATP binding and hydrolysis cycle, and it is thought that interactions with small molecules such as monastrol “lock” this loop into an ADP bound-like conformation. 1, 4, 31, 32 While monastrol has not demonstrated efficacy at pharmacologically relevant concentrations, several compounds that exhibit anticancer activity have advanced to clinical trials. 22, 3338 However, recent characterization of drug-resistant variants of KSP raises concern that tumor cells may develop resistance over time.…”
Section: Introductionmentioning
confidence: 99%